Chronotype differences in timing of energy and macronutrient intakes: A population‐based study in adults. Issue 3 (March 2017) - Maukonen, Mirkka; Kanerva, Noora; Partonen, Timo; Kronholm, Erkki; Tapanainen, Heli; Kontto, Jukka; Männistö, Satu
Abstract : Objective: To examine the association between chronotype and timing of energy and macronutrient intakes in adults. Methods: The study sample included 1, 854 participants from the National FINRISK 2007 and FINDIET 2007 studies, aged 25 to 74 years. Diet was assessed with 48‐hour dietary recalls. Chronotype was assessed with a shortened version of Horne and Östberg's Morningness–eveningness Questionnaire. Associations between chronotype and intakes of energy and macronutrients in the morning (by 10am ) and in the evening (after 8pm ) were analyzed with linear regression and ANOVA followed by Bonferroni post hoc test. Results: In the morning, evening types had lower energy and macronutrient intakes (except for sucrose of which they had a higher intake) than morning types ( P < 0.05), while in the evening, evening types had higher intakes of energy, sucrose, fat, and saturated fatty acids than morning types ( P < 0.05). On the weekend, chronotype differences in evening intakes of energy, sucrose, and fat intake were more pronounced, and evening types had more eating occasions and more irregular meal times than morning types. Conclusions: Postponed energy and macronutrient intake timing of evening types with unfavorable dietary patterns may put them at higher risk of obesity and metabolic disturbances in the future.